2010
DOI: 10.4049/jimmunol.1001613
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic H1N1 Influenza A Viruses Are Resistant to the Antiviral Activities of Innate Immune Proteins of the Collectin and Pentraxin Superfamilies

Abstract: Acquired immune responses elicited to recent strains of seasonal H1N1 influenza viruses provide limited protection against emerging A(H1N1) pandemic viruses. Accordingly, pre-existing or rapidly induced innate immune defenses are of critical importance in limiting early infection. Respiratory secretions contain proteins of the innate immune system, including members of the collectin and pentraxin superfamilies. These mediate potent antiviral activity and act as an initial barrier to influenza infection. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 58 publications
6
100
2
Order By: Relevance
“…RT-PCR was preformed using MyTaq One-Step RT-PCR kit (Bioline) with H1 HAI-and N1 NAI-specific primers as previously described (31). PCR products were purified and sequenced on an ABI3500XL Genetic Analyzer (Applied Biosystems), and sequences were assembled and analyzed using the Lasergene Seqman package (DNAStar7).…”
Section: Rt-pcr and Sequence Analysismentioning
confidence: 99%
“…RT-PCR was preformed using MyTaq One-Step RT-PCR kit (Bioline) with H1 HAI-and N1 NAI-specific primers as previously described (31). PCR products were purified and sequenced on an ABI3500XL Genetic Analyzer (Applied Biosystems), and sequences were assembled and analyzed using the Lasergene Seqman package (DNAStar7).…”
Section: Rt-pcr and Sequence Analysismentioning
confidence: 99%
“…In a mouse model of infection, studies showed that as glycosylation was increased, disease was attenuated in part due to improved recognition and clearance by lung surfactant associated protein-D (SP-D) [52], illustrating that the addition of carbohydrate can have both positive and detrimental effects to the virus. The more recent swine 2009 H1N1 is predicted to have fewer sites for glycosylation than contemporary H1N1 strains and has been shown experimentally to have a single sequon for N-linked glycosylation on the globular head compared to seasonal H1N1 which carry 3-4 sequons [53]. Interestingly, that same study suggested that the loss of N-glycosylation led to resistance of SP-D and mannose binding lectin (MBL) activity.…”
Section: Orthomyxovirus and Paramyxovirusmentioning
confidence: 74%
“…SP-D, a major constituent of human airway fluids (45,61), is a potent inhibitor of highly glycosylated seasonal IAV; however, pandemic viruses are poorly glycosylated and, therefore, are largely resistant to this lectin (27,45,62). PTX3 acts as a SIAa(2,3)-rich "receptor decoy" that is induced following IAV infection, consistent with a role in preventing infection and limiting spread of some pandemic IAV (or avian-origin IAV) in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of virus infectivity by pentraxins was determined by fluorescent-focus reduction in monolayers of MDCK cells, as described (27). Briefly, dilutions of PTX3 or SAP, prepared in TBS containing 10 mM CaCl 2 , were incubated at 37˚C for 30 min with a standard dilution of virus and then added to MDCK cell monolayer for 1 h at 37˚C.…”
Section: Virus Neutralization Assaymentioning
confidence: 99%